Contribution of multidomain titanomagnetite to the intensity and stability of Mars crustal magnetic anomalies - (:unkn) unknown (My University, 2014)
Two basalts with compositions relevant to the crusts of Mars and Earth were synthesized at igneous temperatures and held at 650°C for 21 to 257 days under quartz-fayalite-magnetite ƒO2 buffer conditions. The run products are germane to slowly cooled igneous intrusions, which might be a significant volumetric fraction of the Martian crust and carriers of magnetic anomalies in the Southern Highlands. Both basalts acquired intense thermoremanent magnetizations and intense but easily demagnetized anhysteretic remanent magnetizations carried by homogeneous multidomain titanomagnetite. Hypothetical intrusions on Mars composed of these materials would be capable of acquiring intense remanences sufficient to generate the observed anomalies. However, the remanence would be easily demagnetized by impact events after the cessation of the Mars geodynamo. Coercivity enhancement by pressure or formation of single domain regions via exsolution within the multidomain grains is necessary for long-term retention of a remanence carried exclusively by multidomain titanomagnetite grains.